Characteristics of shale reservoir development under the influence of sedimentary differentiation: A case study of the Cambrian Qiongzhusi Formation in the Deyang-Anyue rift trough of the Sichuan Basin - Wenyi Chen; Bo Wang; Zhenxue Jiang; Dandan Wang; Hui Long; Wenlei Liu; Dadong Liu (Natural Gas Industry B)
The Cambrian Qiongzhusi Formation in the Sichuan Basin harbors significant potential for shale gas harvesting. However, systematic disparities in mineral composition and reservoir architecture have been observed between intra- and extra-trough reservoirs within the Deyang–Anyue Rift Trough. These variations were primarily determined by divergences in the sedimentary environments developed during the evolution of the rift trough, which were a main factor in fostering the heterogeneous distribution of shale gas enrichment found today. However, the genetic mechanisms that govern reservoir heterogeneity across distinct structural domains (intra-trough, trough margin, and extra-trough) remain poorly understood, particularly regarding the coupling relationships between depositional environments, reservoir characteristics, and gas-bearing properties. This study adopts a multidisciplinary approach to investigating this issue that integrates core analysis, well-log interpretations, and geochemical data. Through systematic comparisons conducted using X-ray diffraction mineralogy, organic carbon quantification, and spontaneous imbibition experiments, we characterize the mineral assemblages, organic geochemical signatures, and pore structures found across the three structural domains of the Deyang–Anyue Rift Trough. The key findings are as follows: (1) The depositional environment is the main influence on reservoir distribution and organic matter enrichment, with intra-trough shales exhibiting a higher abundance of organic matter than their trough-margin and extra-trough counterparts. (2) Enhanced brittleness in intra-trough zones correlates with the predominance of biogenic silica therein. (3) Synergistic organic-inorganic interactions govern pore system development. (4) Gas-bearing capacity is jointly determined by effective porosity and organic matter content. These findings establish the rift trough as a preferential exploration target, providing critical geological guidance for optimizing shale gas exploration strategies in the Cambrian Qiongzhusi Formation.